On Záparoan as a valid genetic unity: Preliminary correspondences and the status of Omurano - Carvalho, Fernando O. de (2013)
The Záparoan linguistic family has been so far acknowledged as constituting a genetic group only on the basis of lexical similarity and grammatical parallels. We present here a preliminary statement of recurring sound correspondences holding among the basic lexical and grammatical vocabularies of three languages usually seen as belonging into the Záparoan family: Iquito, Arabela and Záparo. Though still a preliminary effort towards a more complete understanding of the history of this group, this is enough to gain some insight into the sound changes that have acted in the diversification of these languages from their putative common ancestor and to qualify the claims concerning the Záparoan affiliation of a fourth language, Omurano, our conclusion being that no evidence for this hypothesis exists.